Analisis Sistem Pengendalian Intern Terhadap Pengelolaan Keuangan Pada Pemerintah Daerah Kabupaten Pontianak - B51106120, Marlita Putri Yuni (Jurnal KIAFE, 2013)
This study entitled "Analysis of Internal Control System Of Financial Management In Local Government Pontianak regency." Problems in the study were: 1) whether the system of internal control on financial management in local government Pontianak regency has been carried out effectively 2) What factors are causing the ineffectiveness of the system of internal control of financial management in the Government District Pontianak. Research conducted using descriptive method. Techniques of data collection in this research; interviews, observation, research library. The data analysis technique used in this study is an analysis tool; organizational structure, internal control questionnaires, flowchart and compliance testing. Based on the results of the discussion can be concluded that: 1). Internal Control System on financial management in Pontianak District Government through the mechanisms established to obtain the result that the issuance of the SPD has a very effective system with 100% power level, the publication of SPP quite effective with 66.67% system power, publishing SPM ineffective with power system is 36.36%, and has been an effective mechanism SP2D publishing system with 80% power. Broadly speaking, the systems and procedures adopted in accordance with Permendagri No. 13 of 2006 and No. 59 of 2007 Permendagri. On the results of compliance tests conducted there are nine invoices that do not have complete data, the existence and occurrence of mathematical calculations (footing, cross footing, ektension) is good and there is no problem, as well as tests on otoritasasi, there is no shortage of financial expenditure and error, with In other words all data is complete and correct. The factors that led to the financial management of the Pontianak regency government has not been effective internal control system are: the lack of accuracy of the exchequer expenditure and KDP-SKPD in filing fees and filing SPM SPM so that the publication SP2D there are shortcomings and mistakes, rushing authorities signed a document, at the time of filing documents both SPM and SP2D officials are not in place. Keywords : Internal Control System, Financial Management Pontianak District Government